The Juridical Construction of The Obligation of Land Deed Officials to Conduct Field Inspections: Theoretical Foundations, Normative Gaps, and Professional Responsibility in Indonesian Land Law - Yanah Susanti; Zudan Arief Fakrulloh (Ridwan Institute, 2026)
The existence of land as a fundamental object of law demands absolute data accuracy in every transfer of rights. This study examines the juridical problems surrounding the obligation of field inspection, or site inspection, by Land Deed Officials (Pejabat Pembuat Akta Tanah/PPAT), which to date remains without explicit regulation under Indonesia’s positive law. The central issue lies in the tension between formal juridical data and physical field conditions, a discrepancy that frequently gives rise to destructive land disputes. Employing normative legal research through statutory, conceptual, and case analysis approaches, this study identifies a normative gap in Government Regulation No. 37 of 1998 and Government Regulation No. 24 of 2016. The analysis demonstrates that the field inspection obligation constitutes a legal construction derived from the prudential principle and a systematic interpretation of the PPAT’s oath of office, which requires the exercise of due diligence (seksama). Failure to conduct physical verification risks degrading the authenticity of the deed from a public instrument (openbaar document) to a privately executed deed. This study concludes that the transformation of a vague norm into an explicit legal obligation through regulatory reconstruction is urgently required in order to guarantee legal certainty (Rechtssicherheit), substantive justice (Gerechtigkeit), and utility (Zweckmäßigkeit). The principal recommendation is the formalization of standard operating procedures for field inspections, integrated with the electronic land registration system.